Renaissance of Geography Education in Sweden - MURAYAMA, Tomoko (Japanese Journal of Human Geography, 1995)
Until the 1960s, geography was taught as a core subject in Swedish high schools. However in 1966, geography as a school subject was dismantled and combined with science and social studies. After about 30 years of non-existence as a discipline, geography was restored as an independent subject in 1993 with the introduction of a new, comprehensive high school system. Despite the fact that the unification of geography with social studies and science in 1966 spelled the dismantling of geography as an independent discipline, academic geography at that time was already divided into human and natural branches, and many human geographers who had been working to establish their field as a subfield of social studies welcomed the merger into social studies. With the merger of human geography into social studies, descriptive content in geography was removed and replaced with the scientific concepts and theories of the day. However, the status of geography within social studies began to decline. Reasons for this decline include 1) as geography was riding the wave toward applied social science, no consideration from an educational perspective was given of the results of geography as it was incorporated into social science, 2) almost no theoretical or practical research was conducted in geography as a sub-field of social studies, 3) academic geography and geography education became increasingly estranged from one another, and 4) geography became, in effect, irrelevant in the training of social studies teachers, with the result that their understanding and awareness of geography declined, and they themselves did not deal with geography within the subject of social studies. It can be said that in the 1970s and 1980s, geography education in social studies was essentially non-functional. In 1991, when the Swedish high school system was completely reformed, it was decided to restore geography as a school subject. However, this would not have been possible without the existence of geographers who had struggled to restore their discipline to the school curriculum. At the same time, a quantitative reform in education was called for to deal with the diversification of the social demands of a deindustrializing and information-oriented society, the gravity of environmental problems, internationalization, and other issues. Geography which dealt with the relationship between man and nature apparently played an important role environmental education and international studies. One thing is for certain: there was a demand for its revival as a new type of geography education. It cannot be denied that geography is the foundation of geography education, but it should also be stressed that emphasizing only the uniqueness of geography in geography education is behind the times. Therefore, as we look toward the development of a new type of geography education, geography itself, not only in Sweden but elsewhere, is being asked to reevaluate its significance in geography education.